Multiple-site decontamination in critically ill patients requires careful implementation - Yuetian Yu; Bin Lin; Lihui Wang; Chunhui Xu; Cheng Zhu; Yuan Gao (Infectious Medicine)
The EPIC III study showed that 52% of patients admitted to the intensive care unit (ICU) have infectious diseases and that the incidence of ICU-acquired infections is increasing, leading to longer ICU stays and higher mortality rates. Multiple-site decontamination, a type of selective decontamination program, has been associated with a reduction in the incidence of ICU-acquired infection and decreased mortality rates in some critically ill patients. However, the standardized implementation and actual effectiveness of multiple-site decontamination require further investigation.